Management Science Applications in the Bell System - Hardgrave, W. W.; Mac Williams, W. H. (Management Science, 1969)
Bell System applications of management science are reviewed, with examples, under three categories: (a) Facilities—providing the physical communications plant, (b) Operations—concerning both the plant and the organization, and (c) Marketing—determining services to be offered and rates. The facility applications have been the most studied, tend to be the simplest, and have yielded effective engineering solutions using computer programs for many recurring problems. Operations problems tend to be more difficult both to formulate and to solve, and their large size and complexity have frequently led to approximation in both formulation and solution. Marketing 2 problems usually show complex interactions among the level of demand, the plant and services required to satisfy this demand, and the resulting cost of the services. This area has major difficulties in formulation and solution and has been the least studied of the three. However, the marketing area is likely to become the most important one in the future, primarily because of its basic relation to determining the direction of the business.